Navigating Water Security in South Asia: Towards Regional Cooperation and Sustainable Solutions - Chaudhary, Maha Afzal; Tanvir, Muhammad; Choudhry, Muhammad Haroon Munir (Annals of Human and Social Sciences, 2024)
The research examines the costs of non-cooperation and the potential for regional cooperation among South Asian countries considering the intricate water dynamics. South Asia hosts multiple transboundary river basins, including the Indus, Ganges, and Brahmaputra, making water a crucial asset for the socioeconomic growth of the region. The intensifying water scarcity, amplified by extreme climate change phenomena, has heightened competition and tensions among countries sharing these river systems. The study employed qualitative and quantitative methods that used majorly content and discourse analysis. The results of the paper show that the states of South Asia would be more inclined toward collaborating if they could acknowledge their shared interest and understand that the advantages of working together outweigh the conceivable disadvantages. It suggests that the riparian nations of the basin should depoliticize the water and require measures for effective cross-border water management, inclusive policies, and adequate institutional mechanisms while prioritizing sustainable solutions.